The effect of work motivation and emotional intelligence on teacher performance of elementary school teachers in cluster 1 pulau beringin district south oku regency - Tahyuda Tahyuda; Yasir Arafat; Alhadi Yan Putra (Global Econedu, 2021)
This study aims to determine and analyze the effect of work motivation and emotional intelligence partially and collectively on the performance of elementary school teachers in Cluster 1, Pulau Beringin District, South OKU Regency. This research uses quantitative methods. Data were analyzed using multiple linear regression. This study resulted in conclusions 1) Work motivation affects the performance of elementary school teachers in Cluster 1, Pulau Beringin District, South OKU Regency; 2) emotional intelligence affects the performance of elementary school teachers in cluster 1, Pulau Beringin subdistrict, South OKU district; and 3) Work motivation and emotional intelligence together have a significant effect on the performance of elementary school teachers in Cluster 1, Pulau Beringin District, South OKU Regency. The magnitude of the influence of all independent variables on the performance of elementary school teachers in Cluster 1, Pulau Beringin District, South OKU Regency is 89.5%, the remaining 10.5% is influenced by other variables not examined in this study